A consensualidade no processo administrativo disciplinar: entre princípios e práticas - Guimarães, Kaliany Varjão de Santana Oliveira (2025)
The present work aims to examine the possibility of applying consensuality within the scope of the disciplinary administrative process (PAD). Despite the existence of broad legislation encouraging the use of consensuality as a way of resolving legal problems, including in the administrative and disciplinary sphere, there is an unfavorable environment for the establishment of a legitimate consensus, given the PAD's low adherence to the procedural principles extracted from the 1988 Federal Constitution. In this sense, the problems that hinder this consultation will be analyzed, despite the legal and evaluative framework inaugurated with the 1988 Constitution which, among other things, an ethical statute was created that proclaims the requirement for jointly committed behavior and, moreover, it structured the Democratic Rule of Law on the Principle of Human Dignity, the source and foundation of Fundamental Rights and Guarantees. Disciplinary administrative law, when limited to the examination of infractions committed within the scope of Public Administration, must also adapt to constitutional paradigms, so that consensual resolution can be implemented as one of its most effective tools. This study, therefore, will be guided by exploratory and deductive research methods, promoting bibliographic review and document analysis, making a necessary critical examination of specialized legal literature and normative documents.